2012
DOI: 10.1007/s00464-012-2687-4
|View full text |Cite
|
Sign up to set email alerts
|

Totally laparoscopic liver resections for primary and metastatic cancer in the elderly: safety, feasibility and short-term outcomes

Abstract: This retrospective comparative study shows that TLLR performed on elderly for liver neoplasm are feasible and safe and lead to short-term outcomes similar to those of younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…Yet clinical data on laparoscopic liver resection in comparison with open resection in the same setting are lacking. One recent study addressed the feasibility of laparoscopic approach for elderly patients, but their perioperative outcomes in relation to the conventional open approach were not determined . On the other hand, our study demonstrated some of the potential advantages of laparoscopic liver resections over the open approach for this category of patients.…”
Section: Discussionmentioning
confidence: 76%
“…Yet clinical data on laparoscopic liver resection in comparison with open resection in the same setting are lacking. One recent study addressed the feasibility of laparoscopic approach for elderly patients, but their perioperative outcomes in relation to the conventional open approach were not determined . On the other hand, our study demonstrated some of the potential advantages of laparoscopic liver resections over the open approach for this category of patients.…”
Section: Discussionmentioning
confidence: 76%
“…In support of this hypothesis, other reports demonstrated the safety of LLR for elderly. 33,34 Although these reports and the present study were smallscale case studies, our data adds important information regarding the application of LLR for elderly patients.…”
Section: Discussionmentioning
confidence: 77%
“…After exclusion of duplicate or irrelevant references, 53 potentially relevant articles were retrieved. After detailed evaluation of these articles, 27 studies remained for assessment, including a total of 4769 elderly patients ≥70 years of age and 15 855 patients ≤70 years old ( n = 20 624) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…All of the 27 included studies were observational studies, with five prospective, 20 retrospective and two propensity‐matched studies . There were 17 studies which consisted of 50 or more patients in the elderly cohort, while the remaining had fewer than 50 elderly patient . The tumour type was HCC in 10 studies, CLM in nine studies and eight studies had liver resections for other or mixed tumour types …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation